The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/cells9010097
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adenoviral E1A in Transformed Cells as an Additional Factor of HDACi-Dependent FoxO Regulation

Abstract: The adenoviral early region 1A (E1A) protein has proapoptotic and angiogenic activity, along with its chemosensitizing effect, making it the focus of increased interest in the context of cancer therapy. It was previously shown that E1A-induced chemosensitization to different drugs, including histone deacetylases inhibitors (HDACi), appears to be mediated by Forkhead box O (FoxO) transcription factors. In this study, we explore the relationship between E1A expression and the modulation of FoxO activity with HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
3
0
2
Order By: Relevance
“…It has been shown that E1A sensitizes tumor cells with respect to HDIs (SAHA, TSA) more effectively than with respect to other chemotherapy drugs (5-fluorouracil, cisplatin, etoposide, or paclitaxel) [ 13 ]. However, as we have shown earlier, HDI induced degradation of E1A [ 15 ].…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…It has been shown that E1A sensitizes tumor cells with respect to HDIs (SAHA, TSA) more effectively than with respect to other chemotherapy drugs (5-fluorouracil, cisplatin, etoposide, or paclitaxel) [ 13 ]. However, as we have shown earlier, HDI induced degradation of E1A [ 15 ].…”
Section: Introductionmentioning
confidence: 59%
“…Показано, что сенсибилизирующий эффект E1A в отношении цитотоксического действия ИГД (SAHA, TSA) сильнее, чем других химиотерапевтических препаратов (5-фторурацил, цисплатин, этопозид, паклитаксел) [13]. Однако, как показано нами ранее, действие ИГД приводит к деградации Е1А [15].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…However, stress-induced FOXO1 acetylation also arrests FOXO1 ubiquitination and prevents FOXO1 degradation through the ubiquitin-proteasome pathway[ 48 ]. Importantly, acetylation of FOXOs is a reversible process and can be eliminated by histone acetyltransferases and histone deacetylases (HDACs)[ 49 , 50 ]. For example, Sirt1, a class III HDAC, can deacetylate FOXOs and increase their transcription[ 47 ].…”
Section: Characteristics Of Foxo Family Membersmentioning
confidence: 99%